2020
DOI: 10.1111/tbed.13744
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of 7SL‐derived small RNA is a promising alternative for trypanosomosis diagnosis

Abstract: Equine trypanosomosis comprises different parasitic diseases caused by protozoa of the subgenus Trypanozoon: Trypanosoma equiperdum (causative agent of dourine), Trypanosoma brucei (nagana) and Trypanosoma evansi (surra). Due to the absence of a vaccine and the lack of efficacy of the few available drugs, these diseases represent How to cite this article: Verney M, Grey F, Lemans C, et al. Molecular detection of 7SL-derived small RNA is a promising alternative for trypanosomosis diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…The SHERLOCK-7SL assay [15] appeared to be highly speci c in the present study but did not pick up the gHAT case. However, it also merits further evaluation as other studies, although using a different detection format, highlighted the promising diagnostic accuracy of 7SL small RNA detection for Trypanozoon detection in animals [45,46]. Speci city of conventional 18S-PCR is in line with a previous report [23] and although it did not detect the gHAT patient in the present study, its sensitivity has been previously estimated to be su cient [23,27].…”
Section: Discussionsupporting
confidence: 80%
“…The SHERLOCK-7SL assay [15] appeared to be highly speci c in the present study but did not pick up the gHAT case. However, it also merits further evaluation as other studies, although using a different detection format, highlighted the promising diagnostic accuracy of 7SL small RNA detection for Trypanozoon detection in animals [45,46]. Speci city of conventional 18S-PCR is in line with a previous report [23] and although it did not detect the gHAT patient in the present study, its sensitivity has been previously estimated to be su cient [23,27].…”
Section: Discussionsupporting
confidence: 80%
“…Interestingly, defects in quorum sensing pathways have recently been reported in T. evansi and T. equiperdum but also in artificially selected monomorphic lines of T. brucei (Cai et al, 2022). These parasites are normally almost indistinguishable from each other, using a wide range of molecular markers (Gibson et al, 1980;Lun et al, 1992a;Lun et al, 1992b;Lai et al, 2008;Verney et al, 2020), which makes it all the more interesting that these differences map onto the quorum sensing pathways. This implies a link between the acquisition of monomorphism and the loss of quorum sensing and supports the notion that T. evansi and T. equiperdum could have evolved from a malignant (or dedifferentiated) form of T. brucei (Lun et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The 7SL sRNA has also been found to be a sensitive diagnostic marker for equine infections with Trypanosoma brucei equiperdum , the causative agent of dourine; 7SL sRNA signal was detected in horses experimentally infected with T. b. equiperdum before parasite detection by microscopy, and earlier than seroconversion detection using a complement fixation test (CFT), which is the officially-recommended dourine test by OIE ( 30 ). The 7SL sRNA signal remained present in periods of sub-patent parasitaemia but decayed rapidly after trypanocidal treatment, indicating that presence of the marker correlated with active infection and that the test is specific (i.e., correctly identifies absence of infection as negative) ( 31 ). Verney et al also showed that 7SL sRNA is stable at 30°C for 7 days; a highly desirable characteristic for the application of the test in areas with limited or no cold chain capabilities.…”
Section: Introductionmentioning
confidence: 99%